The SARM1 TIR NADase: Mechanistic Similarities to Bacterial Phage Defense and Toxin-Antitoxin Systems - DiAntonio, Aaron; Milbrandt, Jeffrey; Figley, Matthew D. (Frontiers in Immunology, 2021)
The Toll/interleukin-1 receptor (TIR) domain is the signature signalling motif of innate immunity, with essential roles in innate immune signalling in bacteria, plants, and animals(1). TIR domains canonically function as scaffolds, with stimulus-dependent multimerization generating binding sites for signalling molecules such as kinases and ligases that activate downstream immune mechanisms(2). Recent studies have dramatically expanded our understanding of the TIR domain, demonstrating that the primordial function of the TIR domain is to metabolize NAD+. Mammalian SARM1, the central executioner of pathological axon degeneration(3), is the founding member of the TIR-domain class of NAD+ hydrolases(4). This unexpected NADase activity of TIR domains is evolutionarily conserved, with archaeal, bacterial(5), and plant(6,7) TIR domains all sharing this catalytic function. Moreover, this enzymatic activity is essential for the innate immune function of these proteins. These evolutionary relationships suggest a link between SARM1 and ancient self-defense mechanisms that has only been strengthened by the recent discovery of the SARM1 activation mechanism which, we will argue, is strikingly similar to bacterial toxin-antitoxin systems. In this brief review we will describe the regulation and function of SARM1 in programmed axon self-destruction, and highlight the parallels between the SARM1 axon degeneration pathway and bacterial innate immune mechanisms.